Hygienic assessment of professional risk for workers, involved in application of pesticides and tank mixtures in chemical protection of strawberry. - T. I. Zinchenko; I. M. Pelo; S. T. Omelchuk; O. P. Vavrinevych (Medičnì Perspektivi)
When using tank mixtures and pesticides in chemical crop protection systems there exists danger of simultaneous or sequential action ofingredients. It was established that the combined potential risk of the harmful effects of Torero SC preparation on workers is 0.11-0.30 arb.units, Switch 62.5 WG – 0.054-0,065 arb.units, tank mixture 1 – 0.26-0.51 arb.units, tank mixture 2 – 0.26-0.49 arb.units correspondently and does not exceed the allowable value of risk (<1). The combined risk in sequential application of components of chemical protection system of strawberry exceeds allowable values of risk and is 0.954-2.02 arb.units. Ways of occupational risk decrease were proposed and regulations of safe application of tank mixtures and pesticides in chemical protection of strawberrywere substantiated.